Инноватизация как составлющая стратегии модернизации национальной экономики - Симоненко, В.К. (Економічні інновації, 2012)
У статті розглянуто проблеми інноваційного розвитку в Україні. Визначено основні причини ускладнення впровадження інновацій. Запропоновано ключові напрями модернізації економіки держави. In the article the problems of innovative development in Ukraine are considered. Principal reasons of complication of innovations’ introduction are determined. The key trends of modernization of the state economy are offered.